(untitled) (Balthazar, 2021)
If oppressions are interconnected, why shouldn’t the corresponding struggles be interconnected too? Analogies and differences show us how speciesism and patriarchy reinforce and presuppose each other. We often hear about the word intersectionality, but what does it really mean? Understanding how oppressions interact and behave on multiple levels gives us the tools necessary to dismantle the dynamics of power we are still chained to, to rethink our political practices in favor of a worthy work of liberation. Knowing in depth the radical nature of the struggle helps us to imagine otherwise silenced implications and revolutionary solutions.